2013
DOI: 10.1016/j.nbd.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of osteoprotegerin expression in the inner ear causes degeneration of the cochlear nerve and sensorineural hearing loss

Abstract: Osteoprotegerin (OPG) is a key regulator of bone remodeling. Mutations and variations in the OPG gene cause many human diseases that are characterized by not only skeletal abnormalities but also poorly understood hearing loss: Paget’s disease, osteoporosis, and celiac disease. To gain insight into mechanisms of hearing loss in OPG deficiency, we studied OPG knockout (Opg −/−) mice. We show that they develop sensorineural hearing loss, in addition to conductive hearing loss due to abnormal middle-ear bones. OPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
3
35
0
1
Order By: Relevance
“…Dysregulation of this system leads to bony overgrowth and can result in both conductive and sensorineural hearing loss 15 . This soft-tissue-to-bone crosstalk also offers site-specific regulation in the appendicular skeleton, where muscle derived factors regulate bone and vice versa 3133 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of this system leads to bony overgrowth and can result in both conductive and sensorineural hearing loss 15 . This soft-tissue-to-bone crosstalk also offers site-specific regulation in the appendicular skeleton, where muscle derived factors regulate bone and vice versa 3133 .…”
Section: Discussionmentioning
confidence: 99%
“…OPG is secreted from the interdental cells of the spiral limbus, with highest concentrations in the perilymph where osteoclast activity is lowest 14 . The suppression of bone remodeling is lost in OPG deficient mice, which have both sensorineural hearing loss due to demyelination of the cochlear nerve 15 and conductive hearing loss due to bony overgrowth of the ear 14 . This phenotype, however, can be ameliorated with bisphosphonate treatment 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing perilymph TNF‐alpha concentrations should have a stabilizing effect on hair cell populations and hearing, although this has not been scientifically validated. Alternatively, bisphosphonates may directly affect spiral ganglion cells, working to improve their survival …”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that osteoprotegerin (OPG) – a member of the TNF receptor superfamily – is involved in the regulation of neuronal survival in the inner ear (Kao et al ., 2013). Loss of OPG expression causes death of spiral ganglion cells and sensorineural hearing loss, in addition to the previously described conductive hearing loss (Zehnder et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Both TRAIL and TNF‐α regulate inflammation (Bradley, 2008), at least partly by regulating a pro‐inflammatory transcription factor NF‐kB (Secchiero et al ., 2003), and both are involved in auto‐immune diseases (Kollias et al ., 1999; Aktas et al ., 2005). Due to these similarities between TRAIL and TNF‐α, the importance of TNF‐α for cochlear pathobiology, and our finding of OPG's importance for survival and function of spiral ganglion neurons (Kao et al ., 2013), we studied the expression and function of TRAIL and DR5 in the inner ear. Using a combination of techniques – including real‐time quantitative RT–PCR, Western blot, in situ hybridization, organotypic cell culture, and an auditory cell line – we demonstrate a possible role for TRAIL and DR5 in sensorineural degeneration in the inner ear.…”
Section: Introductionmentioning
confidence: 99%